Nature Does the Averaging—In-Situ Produced 10Be, 21Ne, and 26Al in a Very Young River Terrace - Andreas Gärtner; Silke Merchel; Samuel Niedermann; Régis Braucher; ASTER-Team; Peter Steier; Georg Rugel; Andreas Scharf; Loic Le Bras; Ulf Linnemann (Geosciences, 2020)
The concentrations of long-lived in-situ produced cosmogenic nuclides (10Be, 21Ne, 26Al) in quartz obtained from a very recent (~200 a; based on 14C data on organic material) terrace of the Swakop River in Namibia are nearly constant throughout a 322 cm-long depth profile. These findings corroborate earlier hypotheses postulating a homogeneous distribution of these nuclides in freshly deposited river terrace sediments. An averaged nuclide concentration is a crucial and generally assumed prerequisite for the determination of numerical ages of old sediments.